Clinical and demographic features of hidradenitis suppurativa: a multicentre study of 1221 patients with an analysis of risk factors associated with disease severity. (2nd January 2021) - Özkur, E.; Karadağ, A. S.; Üstüner, P.; Aksoy, B.; Eşme, P.; Çalışkan, E.; Akoğlu, G.; Kalkan, G.; Demirseren, D. D.; Polat, M.; Ozden, M. G.; Kılınç, F.; et al.
Summary: Background: Hidradenitis suppurativa (HS) is a chronic, relapsing and debilitating inflammatory disease associated with profound morbidity. Aim: In this multicentre study, we investigated the demographic and clinical features of HS, and determined risk factors of disease severity. Methods: In total, 1221 patients diagnosed with HS from 29 centres were enrolled, and the medical records of each patient were reviewed. Results: The mean age of disease onset was 26.2 ± 10.4 years, and almost 70% ( n = 849) of patients were current or former smokers. Mean disease duration was 8.9 ± 8.4 years with a delay in diagnosis of 5.8 ± 3.91 years. Just over a fifth (21%; n = 256) of patients had a family history of HS. The axillary, genital and neck regions were more frequently affected in men than in women, and the inframammary region was more frequently affected in women than in men ( P < 0.05 for all). Acne (40.8%), pilonidal sinus (23.6%) and diabetes mellitus (12.6%) were the most prevalent associated diseases. Of the various therapies used, antibiotics (76.4%) were most common followed by retinoids (41.7%), surgical interventions (32.0%) and biologic agents (15.4%). Logistic regression analysis revealed that the most important determinants of disease severity were male sex (OR = 2.21) and involvement of the genitals (OR = 3.39) and inguinal region (OR = 2.25). More severe disease was associated with comorbidity, longer disease duration, longer diagnosis delay and a higher number of smoking pack‐years. Conclusions: Our nationwide cohort study found demographic and clinical variation in HS, which may help broaden the understanding of HS and factors associated with disease severity.